The Role of Digital Documentation in Protecting Urban Heritage - Kadhim, Huda; Alsalam, Nadia (Al-Adab Journal, 2025)
The idea of the research came from the importance of historical, and ancient areas with heritage value, as the cities of the world in general and these areas in particular face great and ongoing challenges due to many factors, such as globalization, population explosion, conflict, wars and other human and natural impacts, which requires their preservation and protection through documentation. Documentation is the first step in protecting these areas, especially with the development of equipment and technologies. There has become an urgent need to integrate heritage within the specificity of the current stage, which is expressed in the digital age. From here comes the research problem, which is the lack of knowledge about the role played by digital documentation of areas with important heritage. The research will summarize the concept of heritage, the components of heritage at an urban level, the challenges facing heritage, and clarify the nature of technologies, documentation techniques, and the concept of urban digital documentation, and then classify documentation according to purpose, technology, and implementing agency, while clarifying international experience. For each type, and based on these classifications, the research presented results represented by the diverse and different role of the digital documentation process, and this comes from the diversity of the entity that performs the documentation and the technology used and thus the diversity of roles, but as a result it contributes to protecting and preserving heritage first and ensuring its sustainability for subsequent generations and people’s access to it.